Quantitative NS1 antigen and the severity of dengue virus infections - Ni Made Adi Purnami; Mohammad Juffrie; Made Gde Dwi Lingga Utama (Paediatrica Indonesiana, 2015)
Background Dengue infection is one of the main cause ofmorbidity and mortality in children in Indonesia. Since it is knownthat earlier treatment and supportive therapies can decreased casefatality rate from dengue hemorrhagic fever (DHF), identificationof children who have risks to develop to DHF must be quicklyidentified, mainly in areas of endemic.Objective To find a correlation between increased quantitativesecreted nonstructural protein-1 (sNS1) with clinical course ofsevere dengue infections.Methods This was a cross-sectional study conducted on childrenwith dengue infections in Tropical Infections Division of ChildHealth Department, Sanglah Hospital, Denpasar. Detection ofthe dengue antigen was made by examining sNS1 quantitativeimmuno-assay. Analysis correlation of Spearman test was used tolook the relationship between increased quantitative sNS1 withclinical course of severe dengue infections.Results There was a positive relationship between quantitativesNS1 and clinical course of severe dengue infections with a valueof r = 0.903, P=0.001. Increased sNS1 level had a positivecorrelation with more severe dengue infections.Conclusions Quantitative sNS1 titer has a strong positivecorrelation with clinical course of severe dengue infections.